Contribution of Women in Political Movement of Nepal - Phuyel, Shyamprasad; Ghimire, Taranath (Rupantaran: A Multidisciplinary Journal, 2024)
This article explores the extraordinary contributions made by women to Nepal's political movement, demonstrating their fundamental influence on the political climate of the nation. The study investigates the varied political activism of Nepalese women through an analysis of historical accounts, academic research, and direct testimonies. In Nepal, women have been instrumental in political movements, community mobilization, and advocacy for social and political change. They have actively taken part in protests, rallies, and neighborhood campaigns, pushing back against patriarchal conventions and clamoring for equitable participation in governmental organizations. In order to advance gender equality and women's rights in the political sphere, the article examines the effects of women's organizations, women-led projects, and female activists. It looks at their initiatives to remove social constraints, boost women's political participation, and combat gender-based prejudice. This article also examines the obstacles women have had to overcome while examining the crucial role they have played in Nepal's political movement and their contributions to constitutional changes. The paper offers insights on the empowerment of women within the Nepali political system by a thorough analysis of scholarly research, historical records, and documented experiences.